A Classification and the Life Cycle of Snail Monacha cartusiana (O.F. Müller, 1774) in Iraq/ Baghdad - Al-Doori, Nibrass Lafta; Lafta Al-Doori, Maysaloon; Reham FatheyAli (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Most species of Mollusca lives in salts water, on the shores of seas and lakes and some in fresh water, others are found in deserts, forests and forms and there are 45,000 species . They are invertebrate animals with lateral symmetry, slow-moving and a few of them are fast, like Octopus and Squid and some of them are economic importance. The class Gastropoda are considered the largest class belonging to the Phylum-Mollusca, as it contains more than 80%. Its importance follows from its great diversity and spread in all environments. It has an ecological importance because it plays an great role in ecosystems due to the diversity of its food methods between herbivorous and predatory. Studies on snails in Iraq are very few and modest. Hence the idea of identifying these animals and study there classification and life cycle, and when collecting samples in the early morning hours in home gardens and public gardens. A group of these snails was found and most prevalent in these sites in Baghdad was chosen. It was classified and took pictures of it, then it was raised in industrial environment, and after all the appropriate condition were created for it. It found that in Baghdad this snail does not live more than approximately 150 days on average, and that the average duration off eggs hatching is approximately 14 days, and that the resulting larvae survive form only 40% of resulting larvae after hatching, and that those succeed in reaching puberty do not exceed 14% of the individuals. It is diameter ranges at puberty at an average of 11 mm and the number of turns of shell of the shell is 5.5. This snail is characterized by the edge of opening of shell is red lip. These animals like others are affected by its environment. It was found that this species does not live more than a year, with an average of 195 days. As well as that it bears temperatures from (13-37)°C and that it produces eggs 4-5 times and 21-29 eggs each time.